Cultural Connectedness as Personal Wellness in First Nations Youth - Davis, Ben (Scholarship@Western, 2012)
Adolescent development involves changes in self-concept and identification with different groups or cultural norms. Many First Nations adolescents have additional difficulties due to disconnections with family, schooling and cultural background, as a legacy of colonisation and social marginalisation. The present study used data from the First Nations Regional Longitudinal Health Survey, Youth, Phase 2 to test the hypothesis that connectedness to social and cultural factors would predict lower rates of reported depression in First Nations youth, using a logistic regression analysis. The findings indicated that connectedness to family and school, as well as having a sense of control over one's life did predict wellness. However, spiritual balance, and the rating of local communities as having strengths in the areas of First Nations language use and availability of traditional, cultural events predicted greater instances of depression. These findings are discussed in relation to previous research, and recommendations for further investigation are made.